2016
DOI: 10.1038/nmicrobiol.2016.82
|View full text |Cite|
|
Sign up to set email alerts
|

Platelet-derived growth factor-α receptor is the cellular receptor for human cytomegalovirus gHgLgO trimer

Abstract: Human cytomegalovirus (HCMV) encodes at least 25 membrane glycoproteins that are found in the viral envelope1. While gB represents the fusion protein, two glycoprotein complexes control the tropism of the virus: the gHgLgO trimer is involved in the infection of fibroblasts, while the gHgLpUL128L pentamer is required for infection of endothelial, epithelial and myeloid cells2–5. Two reports suggested that gB binds to ErbB1 and PDGFRα6,7, however these results do not explain the tropism of the virus and were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
236
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 163 publications
(258 citation statements)
references
References 39 publications
22
236
0
Order By: Relevance
“…In all experiments, gO-deficient virus mutants were less impaired in infection of HECs than of HFFs. This incomplete dependency of cell-free infection on gO could either be a characteristic of endothelial cells, e.g., via nonspecific endocytic uptake, or it could indicate that gO has two distinct functions in entry: a direct influence on fusion, which is important for entry into all cell types (21), and a fibroblast specific function, e.g., receptor binding, as suggested by a recent publication (34). A detailed analysis of HCMV-specific parts of gO will help to answer this question.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In all experiments, gO-deficient virus mutants were less impaired in infection of HECs than of HFFs. This incomplete dependency of cell-free infection on gO could either be a characteristic of endothelial cells, e.g., via nonspecific endocytic uptake, or it could indicate that gO has two distinct functions in entry: a direct influence on fusion, which is important for entry into all cell types (21), and a fibroblast specific function, e.g., receptor binding, as suggested by a recent publication (34). A detailed analysis of HCMV-specific parts of gO will help to answer this question.…”
Section: Discussionmentioning
confidence: 97%
“…Immunization of mice with gH/gL/gO leads to full protection from otherwise lethal MCMV infection (33). For HCMV it was recently demonstrated that gH/gL/gO interacts with the cellular receptor platelet-derived growth factor receptor alpha (PDGFR-␣) (34). Taken together, these findings highlight that gO is a promising target for future vaccination strategies.…”
mentioning
confidence: 95%
“…In more detail, gH/gL may be complexed either with pUL128L, giving rise to the PC gH/gL/ pUL128L, or UL74-encoded gO, thus forming the trimeric complex gH/gL/gO, which binds to platelet-derived growth factor receptor a and mediates HCMV entry into HELFs [57][58][59]. Thus, gH/gL/gO and PC were considered to represent two mutually exclusive cell entry complexes, as suggested by mass spectrometry and mutagenesis analysis [60].…”
Section: Genetic Determinants Of Endothelial Cells and Leukocyte Tropismmentioning
confidence: 99%
“…However, gO and the UL128-131 gene products were reported to compete for binding of gH/gL, thus influencing the ratio of gH/gL/ gO to gH/gL/UL128-131 within virions as well as the HCMV cell tropism [61,62]. As a result, gH/gL/gO was also found to be required for entry into epithelial cells [57,63,64].…”
Section: Genetic Determinants Of Endothelial Cells and Leukocyte Tropismmentioning
confidence: 99%
“…Fibroblast viral entry requires gB and a trimeric complex of glycoproteins gH, gL, and gO, whereas viral entry into endothelial, epithelial, and dendritic cells requires an additional pentameric complex (pentamer) of gH, gL, UL128, UL130, and UL131 (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Consequently, antibodies directed against gB, gH/gL, or gO impair viral entry into fibroblasts and endothelial and epithelial cells, whereas antibodies that specifically target the pentamer selectively block viral entry into epithelial and endothelial cells (28,33,(35)(36)(37). Following natural infection, the latter activity is dominant, as the serum neutralizing titers measured with epithelial cells are significantly higher than those measured using fibroblasts (38)(39)(40)(41).…”
mentioning
confidence: 99%